Constructions of almost difference sets from finite fields - Ding, Cunsheng; Pott, Alexander; Wang, Qi (Designs, codes, and cryptography, 2014)
Almost difference sets are an interesting subject of combinatorics, and have applications in many areas of engineering such as CDMA communications, error correcting codes and cryptography. The objective of this paper is to present some new constructions of almost difference sets, together with several results on the equivalence relation.